(untitled) (Clinics, 2023)
Objective: Identify the one-year survival rate and major complications in patients submitted to pneumonectomy for infectious disease. Methods: Retrospective data from all cases of infectious disease pneumonectomy over the past 10 years were collected from two reference centers. The authors analyzed: patient demographics, etiology, laterality, bronchial stump treatment, presence of previous pulmonary resection, postoperative complications in the first 30 days, the treatment used in pleural complications, and one-year survival rate. Results: 56 procedures were performed. The average age was 44 years, with female predominance (55%). 29 cases were operated on the left side (51%) and the most frequent etiology was post-tuberculosis (51.8%). The overall incidence of complications was 28.6% and the most common was empyema (19.2%). Among empyema cases, 36.3% required pleurostomy, 27.3% required pleuroscopy and 36.3% underwent thoracoplasty for treatment. Bronchial stump fistula was observed in 10.7% of cases. From all cases, 16.1% were completion pneumonectomies and 62.5% of these had some complication, a significantly higher incidence than patients without previous surgery (p = 0.0187). 30-day in-hospital mortality was (7.1%) with 52 cases (92.9%) and 1-year survival. The causes of death were massive postoperative bleeding (1 case) and sepsis (3 cases). Conclusions: Pneumonectomy for benign disease is a high-risk procedure performed for a variety of indications. While morbidity is often significant, once the perioperative risk has passed, the one-year survival rate can be very satisfying in selected patients with benign disease.